Decrease in CO2 Emissions in Obtaining Polymer‐Grade Propylene by Extractive Distillation. Issue 9 (1st August 2022) - Cruz-Valdez, Jesús Alonso; Patiño-Herrera, Rosalba; González-Alatorre, Guillermo; Louvier-Hernández, José Francisco; Martínez, Adriana Avilés; Perez, Elías
Abstract: To separate propylene from propane, whose boiling points are very close, leads to challenges, especially if it is intended to achieve higher energy efficiencies, reduce process expenses, and diminish environmental impacts. Polymer‐grade propylene can be obtained through an extractive distillation process, using 90 wt % of acetonitrile (ACN) as main solvent and 10 wt % of ethylenediamine (EDA) or methyl ethyl ketone or ethanol as co‐solvent, favoring the separation of propylene with purity greater than 99.60 mol % due to the increase of the relative volatility of propane. Compared to the use of aqueous N ‐methyl‐2‐pyrrolidone (NMP) as extraction solvent, ACN‐EDA solvents have shown to be able to achieve savings of 8.09 % in total annual cost and 5.95 % in CO2 emissions. The results demonstrate that the extractive distillation process using ACN‐EDA can reduce process costs as well as CO2 emissions compared to the same process with aqueous NMP. Abstract : Propylene after ethylene is the most important raw material for the preparation of other organic products. Separating the mixture propylene and propane, which is extracted in refineries and whose boiling points are very close, is a challenge. By applying the extractive distillation process, propylene with more than 99.6 mol % purity was obtained, reducing CO2 emission and total annual cost.